Primary school reopening and parental work - Haeck, Catherine; CRDCN (My University, 2023)
The researchers examine working trends of parents in response to primary school reopening using a household-level framework to observe impacts on single mothers and fathers and dual-parent mothers and fathers, separately. Trends in parental work are assessed from January 2017 to January 2021, based on three labour market outcomes: employed and at work, employed and absent from work and hours worked.
Keywords: Children & youth; Education, training & learning; Health; Labour; Population & demography